2010
DOI: 10.1016/j.drugalcdep.2009.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Geographic clustering of underage drinking and the influence of community characteristics

Abstract: The aim of this paper was to examine the extent to which underage drinking clusters geographically in a sample of communities, and to investigate the manner in which community-level contexts are related to this process. We used data from a randomized community trial of underage drinking to provide the first quantitative estimates of the magnitude of the geographic clustering of underage drinking based upon pairwise odds ratios (PWORs). The Enforcing Underage Drinking Laws Randomized Community Trial provided da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 73 publications
2
32
0
2
Order By: Relevance
“…Clustering was estimated within communities using the ALR method developed by Carey and colleagues (1993) and implemented by other researchers in the area of drug use (e.g., Bobashev and Anthony, 2000;Delva et al, 2000;Anthony, 2000, 2003;Reboussin et al, 2010Reboussin et al, , 2011Wells et al, 2009). PWOR estimated from ALR refl ect how strongly behaviors co-occur in communities (referred to as clustering).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Clustering was estimated within communities using the ALR method developed by Carey and colleagues (1993) and implemented by other researchers in the area of drug use (e.g., Bobashev and Anthony, 2000;Delva et al, 2000;Anthony, 2000, 2003;Reboussin et al, 2010Reboussin et al, , 2011Wells et al, 2009). PWOR estimated from ALR refl ect how strongly behaviors co-occur in communities (referred to as clustering).…”
Section: Methodsmentioning
confidence: 99%
“…This will provide evidence as to whether social factors have infl uence over the individual disadvantage of youth that predisposes them to participate in risky drinking (Massey, 1996;Wilson, 1996). Several individual-level characteristics of the participants-some of which mark varying levels of vulnerability, predisposition, or risk of underage drinking and that were found in our previous analyses of these data to be important (Reboussin et al, 2010;Song et al, 2009)-were considered. These include age, gender, race, parental education, and family structure as defi ned in Table 2.…”
Section: Measures-demographic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, most community-level explanations of crime and delinquency have emphasized the causal role that economic deprivation plays in explaining high crime and delinquency rates in impoverished communities (e.g., social disorganization theory, relative deprivation, concentrated disadvantage). However, multilevel studies of neighborhood disadvantage and substance use have produced mixed results, with some studies finding economic disadvantage to be positively associated with substance use behaviors (e.g., Hoffmann, 2002; Chuang, Ennett, Bauman, & Fosheee, 2005; Frank, Cerda, & Rendon, 2007; Henry & Slater, 2007; Xue, Zimmerman, & Caldwell, 2007; Whaley, Smith, & Hayes-Smith, 2011; see Gardner, Barajas, & Brooks-Gunn 2010 for a comprehensive review), while others have found that community affluence , rather than disadvantage is associated with a higher likelihood of adolescent substance use (Snedker, Herting, and Walton 2009; Reboussin, Preisser, Song, & Wolfson, 2010; Cronley et al, 2012). Likewise, despite the reality that many racial and ethnic minorities disproportionately reside in economically disadvantaged communities, cumulative evidence suggests that most racial and ethnic minority youth in America use substances less frequently than (both non-Hispanic and Hispanic) whites (SAMHSA 2009; Wallace, Vaughn, Bachman, O'Malley, Johnston & Schulenberg, 2009).…”
Section: Introductionmentioning
confidence: 99%